GAIT PERFORMANCE MEDIATES THE RELATIONSHIP BETWEEN PAIN AND FALLS AMONG OLDER ADULTS: THE MOBILIZE BOSTON STUDY II. (11th November 2018) - Cai, Y; Leveille, S; Hausdorff, J; Dong, Z; Shi, L; Manor, B; McLean, R; Bean, J
Abstract: Chronic musculoskeletal pain is linked to increased fall risk among elders. Older adults with chronic pain also experience mobility limitations. This prospective study examined the mediating effect of gait measures in the relationship whereby pain leads to falls. In the MOBILIZE Boston Study II of adults aged ≥70y living in the Boston area, 294 completed the gait assessment. Chronic musculoskeletal pain was classified as multisite, single site, or no pain, based on pain assessment of the hand/wrists, shoulders, back, hip, knees and feet. The gait assessment included walking under each of 3 conditions, quiet walk (QW), easy dual task (DTE), and hard dual task (DTH), on a 16-foot sensored gait mat. Participants were instructed to subtract aloud from 100 by 5's (DTE) and 3's (DTH) while walking at a normal pace. Following baseline assessments of pain and gait, monthly fall calendars were collected over 2 years. Multivariable negative binomial models were performed to determine associations between pain and fall rates, adjusting for sociodemographic and health characteristics. Mediation effects of gait measures on the pain-fall relationship were evaluated using the Sobel test. Multisite pain was associated with a 51% increased risk of falls compared to no pain (adj. IRR=1.51, 95% CI: 1.51–2.10). A number of gait parameters mediated (p-value<0.05) the pain-falls relationship including coefficients of variation for stride time, stride length, and swing time. No mediating effects of DT decrements were found. Chronic musculoskeletal pain may contribute to increased gait variability and thereby increased risk of falls among older adults.